(:unas) unassigned - Roman Sotner; Jan Jerabek; Norbert Herencsar; Tomas Zak; Winai Jaikla; Kamil Vrba (My University, 2015)
Modified current differencing unit (MCDU) and its simple filtering application are introduced in this paper.Modification of the well-known current differencing unit consists in weighted difference of both input currents controlled by adjustable current gain, controllable intrinsic resistance of both current input terminals, and availability of additional voltage terminal(s).Definition of MCDU therefore requires four adjustable parameters (B 1 , B 2 , R p , R n ).A presented active element offers and combines benefits of electronically controllable current conveyor of second generation and current differencing unit and allows synthesis of interesting adjustable applications, which are not available by classical approaches based on simple elements.MCDU brings variability of the transfer function into the structure.It provides several transfer types without necessity of input or output node change by simple electronic tuning.A presented structure represents so-called reconnection-less reconfigurable current-mode filter for realization of all-pass, inverting highpass, low-pass and direct transfer response.Behavioral model of the MCDU was prepared and carefully tested in filtering application.Spice simulations and measurements confirmed theoretical assumptions.
Keywords: null